2009
DOI: 10.1002/jclp.20559
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized trial of a cognitive‐behavioral therapy and hypnosis intervention on positive and negative affect during breast cancer radiotherapy

Abstract: Breast cancer radiotherapy can be an emotionally difficult experience. Despite this, few studies have examined the effectiveness of psychological interventions to reduce negative affect, and none to date have explicitly examined interventions to improve positive affect among breast cancer radiotherapy patients. The present study examined the effectiveness of a multimodal psychotherapeutic approach, combining cognitive-behavioral therapy and hypnosis (CBTH), to reduce negative affect and increase positive affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 38 publications
3
51
0
9
Order By: Relevance
“…Empirical literature suggests that a multimodal psychotherapy approach that combines cognitive behavior Finding Positive Meaning After Loss 253 therapy and hypnosis is effective in reducing negative affect and increasing positive affect during radiotherapy among breast cancer patients (Schnur et al, 2009). Further, in a longitudinal study, Moskowitz, Folkman, Collette, and Vittinghoff (1996) found that positive reappraisal was significantly associated with positive affect during AIDS-related care-giving and bereavement.…”
Section: Discussionmentioning
confidence: 96%
“…Empirical literature suggests that a multimodal psychotherapy approach that combines cognitive behavior Finding Positive Meaning After Loss 253 therapy and hypnosis is effective in reducing negative affect and increasing positive affect during radiotherapy among breast cancer patients (Schnur et al, 2009). Further, in a longitudinal study, Moskowitz, Folkman, Collette, and Vittinghoff (1996) found that positive reappraisal was significantly associated with positive affect during AIDS-related care-giving and bereavement.…”
Section: Discussionmentioning
confidence: 96%
“…Although some studies have shown that radiotherapy is generally better accepted than what may be expected [3,4] and than other treatments [5], other studies have also shown that it can be associated with emotional distress [6][7][8] and especially anxiety [3,5,7,9]. Ten to twenty percent of patients with cancer experience anxiety before the start of radiotherapy [7] and 20-50% of patients feel anxious during the first days of treatment; these feelings tend to decrease throughout the course of treatment, although results have varied greatly across studies [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…More recently the combination of CBT and hypnosis effectively decreased negative affect and improved positive affect in breast cancer patients receiving radiation therapy. 24 CBT changed maladaptive cognitions and behaviors in these patients while leading to more adaptive cognitive process; hypnosis (involving direct suggestion of decreasing negative affect and increasing positive affect) also led to improvement. In those infected with HIV, rates of depression are high, and co-morbidity is associated with increased rates of risky behaviors, poorer disease outcome (e.g., with a decreased CD4 count, an increased viral load, an increased progression to AIDS, and an increased mortality rate), and poor treatment adherence.…”
Section: Additional Psychotherapeutic Techniques In the Medically Illmentioning
confidence: 96%